Ranking the Cities of Sistan and Baluchestan Province Based on Health and Treatment Indices Using the TOPSIS Method - Mohamad Reza Shahraki; Nastaran Abbasi Hasanabadi (Tehran University of Medical Sciences, 2019)
Background and Aim: One of the important dimensions of access to health services is uniform distribution. A survey on the distribution of health and treatment indices in different regions reveals inequalities in order to reduce inequalities. The study aims to rank the cities of Sistan and Baluchestan province from the perspective of access to healthcare services. Materials and Methods: This is a descriptive-applied and cross-sectional study. The data were collected from the database of Statistical Center of Iran. The studied indices were weighted by Shannon entropy method, and the ranking of cities was done by TOPSIS method. The distribution of health services among the cities was shown by Spearman and Kendall correlation coefficient. Also, with the coefficient of variation, the important indices for creating imbalances were determined. Results: The results of TOPSIS method showed a significant difference between the levels of access to health services indices. Zabol and Zahedan cities ranked first and second, and the cities of Ghasreghand, Sibsuran and Fanuj were in the last rank, respectively. Among the factors that led to a level difference, the number of PhDs, laboratory sciences doctors and rehabilitation centers caused the greatest difference between the cities. The findings show that there is little correlation between demographic rank and access to healthcare services, and health services are not distributed equitably according to the population. Conclusion: More attention to cities that are ranked below the level of access to healthcare resources is needed. More healthcare resources should be given to this province because there are few healthcare indices relative to its population.